2012
DOI: 10.1227/neu.0b013e31826cdd3b
|View full text |Cite
|
Sign up to set email alerts
|

Cable-Strengthened C2 Pedicle Screw Fixation in the Treatment of Congenital C2-3 Fusion, Atlas Occipitalization, and Atlantoaxial Dislocation

Abstract: This technique is a promising option for the treatment of AAD with congenital C2-3 fusion and occipitalization. Biomechanically, this technique can reduce the occipital-axial motion significantly compared with occiput-C2 fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
0
6
0
5
Order By: Relevance
“…1,33 The former may not be prominent in reducible AAD, but nevertheless, the antishearing effect of the holding force of the screws is important in cases of fixed AAD with BI. Wang et al 33 reported a case of C2 pedicle screw breakage in a patient with fixed AAD with BI, which occurred even though the fixation of the occiput-C2 pedicle screw was strengthened by a titanium cable between the C2 pedicle screw and the C3 spinous process.…”
Section: Advantages Of This Techniquementioning
confidence: 99%
“…1,33 The former may not be prominent in reducible AAD, but nevertheless, the antishearing effect of the holding force of the screws is important in cases of fixed AAD with BI. Wang et al 33 reported a case of C2 pedicle screw breakage in a patient with fixed AAD with BI, which occurred even though the fixation of the occiput-C2 pedicle screw was strengthened by a titanium cable between the C2 pedicle screw and the C3 spinous process.…”
Section: Advantages Of This Techniquementioning
confidence: 99%
“…В настоящее время наиболее надежной является задняя фиксация с использованием полиаксиальных винтов и стержней. Оптимальным уровнем фиксации в большинстве случаев является чешуя затылочной кости -С 2 позвонок [12,13,38]. При атлантоаксиальном блокировании наиболее эффективной в большинстве случаев является фиксация С 1 -C 2 по Harms [5, 15,18].…”
Section: хирургия позвоночникаunclassified
“…При атлантоаксиальном блокировании наиболее эффективной в большинстве случаев является фиксация С 1 -C 2 по Harms [5, 15,18]. Наибольшие сложности возникают при стабилизации краниоцервикального отдела на фоне врожденных аномалий развития, когда гипоплазия костных структур позвонков не позволяет использовать их в качестве опорных точек фиксации и когда есть высокий риск нейроваскулярных повреждений [1,9,12,13,16,30,38]. Данные обстоятельства существенно ограничивают выбор способов введения винтов.…”
Section: хирургия позвоночникаunclassified
See 1 more Smart Citation
“…Атлантоаксиальные дислокации (ААД) на фоне врожденных аномалий краниовертебрального перехода наиболее широко изучены в Индии и Китае [17,27,[36][37][38]. Известно, что смертность при травматических ААД составляет 60-80 % из-за резкого сдавления спинного мозга и ствола головного мозга [14,35,39], смертность при ААД на фоне врожденных аномалий краниовертебрального перехода не известна, но описана частота возникновения миелопатии -от 40 до 100 % [17,25,28,29,36]. Факторами риска неврологической нестабильности при ААД являются травмы и избыточное сгибание в шейном отделе.…”
unclassified